Applications of CRISPR/Cas tools in improving stress tolerance in Brassica crops - Ton, Linh Bao; Qayyum, Zuhra; Amas, Junrey; Thomas, William J. W.; Edwards, David; Batley, Jacqueline; Dolatabadian, Aria (Frontiers in Plant Science, 2025)
Brassica species, which include economically important Brassica crops grown around the globe, are important as popular vegetables, forage, and oilseed crops, supplying food for humans and animals. Despite their importance, these crops face increasing challenges from biotic and abiotic stresses, exacerbated by climate change and the evolving threat of crop pathogens. Enhancing crop resilience against these stresses has become a key priority to ensure stable crop production. Recent advancements in genomic studies on Brassica crops and their pathogens have facilitated the deployment of CRISPR/Cas systems in breeding major Brassica crops. This review highlights recent progress in CRISPR/Cas-based gene editing technologies to improve resistance to pathogens and enhance tolerance to drought, salinity, and extreme temperatures. It also summarises the molecular mechanisms underlying crop responses to these stresses. Furthermore, the review discusses the workflow for employing the CRISPR/Cas system to boost stress tolerance and resistance, outlines the associated challenges, and explores prospects based on gene editing research in Brassica species.